Reversible Demyelination, Blood-Brain Barrier Breakdown, and Pronounced Neutrophil Recruitment Induced by Chronic IL-1 Expression in the Brain - Ferrari, Carina Cintia (2004)
Interleukin-1  (IL-1) expression is associated with a spectrum of neuroinflammatory processes related to chronic neurodegenerative diseases. The single-bolus microinjection of IL-1 into the central nervous system (CNS) parenchyma gives rise to delayed and localized neutrophil recruitment, transient blood-brain barrier (BBB) breakdown, but no overt damage to CNS integrity. However, acute microinjections of IL-1 do not mimic the chronic IL-1 expression, which is a feature of many CNS diseases. To investigate the response of the CNS to chronic IL-1 expression, we injected a recombinant adenovirus expressing IL-1 into the striatum. At the peak of IL-1 expression (days 8 and 14 post-injection), there was a marked recruitment of neutrophils, vasodilatation, and breakdown of the BBB. Microglia and astrocyte activation was evident during the first 14 days post-injection. At days 8 and 14, extensive demyelination was observed but the number of neurons was not affected by any treatment. Finally, at 30 days, signs of inflammation were no longer present, there was evidence of tissue reorganization,the BBB was intact, and the process of remyelination was noticeable. In summary, our data show that chronic expression of IL-1, in contrast to its acute delivery, can reversibly damage CNS integrity and implicates this cytokine or downstream components as major mediators of demyelination in chronic inflammatory and demyelinating diseases.